CIVILIZED COEXISTENCE IN THE HEAVENLY RELIGIONS: A HISTORICAL APPROACH AND A SOCIAL VISION IN THE REALITY OF THE TIMES - Bensefia Mohamed,; Maaziz Abdelkader,; Sekkakou Houria,; Mezzi Khadija, (International Journal of Innovative Technologies in Social Science, 2025)
The true and pure monotheistic religions of distortions and positive texts emphasized the need for understanding, acquaintance and cooperation between people, but while recognizing the principle of difference between these races, and that is in the service of humanity and its interests, and the basis of that justice and equality, and we as Muslims ordered Islam and the Holy Quran, which God has saved from any distortion or falsification, to preserve that coexistence, and to set the ideals in coexistence with others and preserve their rights, and history is a testament to that and history. This framework includes the objectives of this article entitled: The message of civilized coexistence in the heavenly religions: a historical approach and a social vision in the reality of the times, the first part of which we try to focus on that noble message in all the heavenly religions and approach them through models witnessed by history; The strong dominated the weak and violated his sanctities and ate his rights, and the grinding wars and seditions that are prevalent nowadays are only the result of the interruption of the rope of coexistence and civilized communication, which was and still is The Pure Source Islam through the verses of the Holy Quran and the Prophet's Sunnah.